Ответы и объяснения

 \frac{4,9:  1\frac{2}{5}+ 3\frac{5}{6}  }{3,5-1,8* 4\frac{1}{6} } : (-1\frac{7}{15} )+ \frac{ (6\frac{2}{5} -10)*(-1,5)}{3,25-1 \frac{9}{20} } = 4\frac{1}{4} =4,25

1)4,9:1 2/5=49/10:7/5=49/10*5/7=7/2
2)7/2+3 5/6=7/2+23/6=21/6+23/6=44/6
3)1,8*4 1/6=18/10*25/6=15/2
4)3,5-15/2=3,5-7,5=-4
5)44/6:(-4)=44/6*(-1/4)=-11/6
6)-11/6:(-1 7/15)=11/6:22/15=11/6*15/22=5/4
7)6 2/5-10=6 2/5-9 5/5=-3 3/5
8)-3 3/5*(-1,5)=18/5*15/10=27/5
9)3,25-1 9/20=3 25/100-1 9/20=3 1/4-1 9/20=13/4-29/20=65/20-29/20=
=36/20=9/5
10)27/5:9/5=27/5*5/9=3
11)5/4+3=1 1/4+3=4 1/4=4,25


0.0
0 оценок
0 оценок
Оцени!
Оцени!
В ответе получается 4,25
сейчас добавлю ответ в десятичной дробью
готово
Большое спасибо, вы меня выручили
пожалуйста